1991
DOI: 10.1016/0014-5793(91)81190-j
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol and lipid metabolism Differential effects on liver and brain microsomes

Abstract: We have determined the effect of prolonged ethanol treatment on several enzyme activities related to lipid metabolism in chick-brain and liver microsomes. Ethanol incrcascd microsome cho!esterol levels in both organs. The treatment caused a marked increase in the hepatic HMG-CoA rcductase and ACAT activities while in the brain a clear decrease was found in these enzyme activities. At the same time the aaivity of reacylation of phospholipids. was clearly mcdificd in both brain and liver. Thus, while in the live… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
2
9
0
Order By: Relevance
“…Regarding the synthesis of esterified cholesterol from oleate, the results set out in Table 4 show that the levels of radioactivity from oleate in the hepatocytes of rats fed with ethanol were 70% higher than in those of the controls. These results agree with those of other authors in rat liver [29] and chicken liver [30], where chronic alcohol administration was reported to increase the activity of acyl CoA:cholesterol acyltransferase (ACAT), the microsomal enzyme responsible for the esterification of cholesterol. This enzyme acylates endogenous free cholesterol and thus an increase in its activity may merely reflect greater substrate availability.…”
Section: Resultssupporting
confidence: 83%
“…Regarding the synthesis of esterified cholesterol from oleate, the results set out in Table 4 show that the levels of radioactivity from oleate in the hepatocytes of rats fed with ethanol were 70% higher than in those of the controls. These results agree with those of other authors in rat liver [29] and chicken liver [30], where chronic alcohol administration was reported to increase the activity of acyl CoA:cholesterol acyltransferase (ACAT), the microsomal enzyme responsible for the esterification of cholesterol. This enzyme acylates endogenous free cholesterol and thus an increase in its activity may merely reflect greater substrate availability.…”
Section: Resultssupporting
confidence: 83%
“…Membranes isolated from chronically ethanol-treated mice proved resistant to the fluidizing effect of ethanol (Chin and Goldstein 1977), and in parallel, the cholesterol content of the membranes was increased (Chin et al 1978). Chronic ethanol treatment also induced a significantly increased cholesterol level in microsomes isolated from chicken brain and liver (Sanchez-Amate et al 1991). Erythrocyte membranes isolated from chronic alcoholics exhibited an increase in cholesterol content and a decrease in membrane fluidity (Parmahamsa et al 2004).…”
Section: Heat Shock Proteins and Their Roles In Membrane Protectionmentioning
confidence: 99%
“…The formation of the phospholipid phosphatidylethanol (PEth) during ethanol exposure has been implicated in the pathogenesis of alcohol-induced organ damage [7]. Hepatic triacylglycerol accumulations have been described in chronic alcoholism [12]; however, reports on the effects of ethanol administration on the biosynthesis of cellular phospholipids are few and contradictory [4,10,16]. Several researchers have found that ethanol affects the incorporation and distribution of various exogenously supplied substrates in different ways.…”
mentioning
confidence: 99%